Spectroscopic study and application of the interaction mechanism of meloxicam with trypsin. Issue 6 (3rd July 2019) - Liu, Bao-Sheng; Cheng, Xu; Zhang, Hong-Cai; Ma, Li-Hua; Wang, Chun-Dan
Abstract: In order to explore the interaction between meloxicam and trypsin, the interaction mechanism between meloxicam and trypsin was studied by fluorescence spectrum, UV-vis absorption spectrum, circular dichroism spectrum, and molecular docking simulation under the experimental condition of pH = 7.40. The results of spectral experiments showed that meloxicam could effectively quench the internal fluorescence of trypsin in the form of static quenching, formed a stable complex at 1:1, and changed the conformation of trypsin. The results of thermodynamic constant showed that Δ G  < 0, indicating that the reaction is spontaneous, Δ H  < 0, Δ S  > 0 indicates that the main force type of the binding system was hydrophobic interaction and hydrogen bonding. Molecular docking technique showed that the best binding site between meloxicam and trypsin was near the catalytic active center of trypsin, and the interaction between them changed the microenvironment of amino acid residues in the catalytic active center of trypsin. The mathematical model of drug and protein showed that when the concentration ratio of meloxicam to trypsin was 1:1, the protein binding rate of the binding system was 5.15%. The concentration ratio of meloxicam to trypsin was 30: 1, and the protein binding rate was 45.4%. The results showed that when the drug concentration was high, the binding effect of the system had a great influence on the concentration of free trypsin.